Cardiovascular Risk Assessment and Profiling among Employees of Tertiary Care Rural Hospital: Central India - Anjalee Chiwhane1, Gajendra Agrawal2 , Joel Joy Thomas3 , Saurbh Hadke4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Cardiovascular risk factors are the major cause of mortality and morbidity. WHO STEPSinstrument is a standard tool proposed for surveillance of Non-Communicable Diseases (NCD) risk factors.The study was aimed to assess risk factors for cardiovascular diseases in the employees of tertiary carehospital using WHO STEPS instrument.Materials and Method: WHO “STEPwise approach to surveillance of non-communicable diseases”methodology was used to conduct a cross-sectional survey among 290 employees aged 20-60 years.Results: The mean age of the study population was 39.05 out of which men constituted 52.06%. There werethe almost equal proportion of males and females with a slight male preponderance (52.06% vs. 47.93%).Family history of hypertension 22.07%, diabetes 20%, history of CVD deaths 10%, current smokers 15.52%,alcohol intake 38.28%, tobacco consumption 41.03 %, obese & overweight (?23 kg/m2) 44.49% were theprevalent major cardiovascular risk factors. 3.08% had a >10% risk of developing CVD in next 10 years.Conclusion: High prevalence of cardiovascular risk factors was seen which can lead to increased morbidityand mortality. Regular health checkup camps should be conducted to combat the disease burden and createawareness.